Limites do ensino de dança na formação do professor de Educação Física - Pereira, Mariana Lolato [UNESP]; Hunger, Dagmar Aparecida Cynthia França [UNESP] (Universidade Estadual Paulista (Unesp), Instituto de Biociências, 2009)
The dance is one of the cultural content of body movement. But it is known, by means of literature and researches, that the training of teachers of Physical Education has submitted this content limits, damaging their future education in schools. This article discusses these limits and their possible solutions, ruled itself for both in literature and analysis on data collected in search of the Masters PEREIRA (2007). In this analysis it was felt that the dance is little in this Fitness because of graduate students have little experience inside and outside the school environment, because many parents, teachers and students have to dance with prejudice, and because do not feel prepared to deal with this content in schools. It appears that this may be due to the hegemony of sports in physical education, and some misunderstandings when you think the goals and content of dance in physical education.

A dança é um dos conteúdos da cultura corporal de movimento. Mas sabe-se, por meio da literatura e de pesquisas realizadas, que na formação dos professores de Educação Física este conteúdo tem apresentado limites, prejudicando seu futuro ensino nas escolas. Este artigo discute estes limites e suas possíveis soluções, pautando-se para tanto em análise bibliográfica e em dados coletados em pesquisa de mestrado de PEREIRA (2007). Nesta análise notou-se que a dança está pouco presente na Educação Física porque os alunos da graduação têm pouca vivência dentro e fora do ambiente escolar, porque muitos pais, professores e alunos têm preconceito com a dança, e porque não se sentem preparados para lidar com este conteúdo no ensino escolar. Conclui-se que isso talvez se deva à hegemonia do esporte na educação física, e a alguns equívocos quando se pensa nos objetivos e conteúdos da dança na educação física.
Limits of dance's teach in the formation of Physical Education teacher
Keywords: Physical Education; Professional Formation; Dance